TELAAH INSENTIF PAJAK PENERBITAN BUKU - Maxensius Tri Sambodo; Ahmad Helmy Fuady; Muhammad Soekarni; Nika Pranata; Mahmud Thoha; Darwin Syamsul Bahri; Sairi Erfanie; Firmansyah Firmansyah; Ernany Dwi Astuty; Saiful Hakam; Syarif Hidayat; Ari Juliano Gema; Sabartua Tampubolon; Linda Suryani (Bina Ekonomi, 2018)
ABSTRACTThe creative economy is expected to be increasingly able to improve the quality of national economic development. The publishing sector which is one of 16 (sixteen) creative industry fields is expected to play a more important role to educate people. Thus, it is necessary to develop supporting publishing industry in Indonesia. This article is intended to answer the following five issues: (i) how are the developments, obstacles, opportunities and challenges in the publishing activities? (ii) what is the value chain of publishing business, and how is the tax policy in each chain? (iii) how should tax book publishing incentives be provided? (iv) what is the impact of providing tax incentives on the prospects of a publishing business? (v) how can the provision of tax incentives encourage the development of the publishing sector and the competitiveness of its industry? This study uses a mixed method approach and information deepening is carried out in 7 provinces in Indonesia. This article has resulted two special findings: (i) identifying crucial issues in the book publishing industry; and (ii) produce a formulation of government policy recommendations, specifically to provide tax incentives to encourage the growth of the publishing sector.Keywords: creative economy; publishing book; tax incetives